Entry, Industry Growth, and the Microdynamics of Industry Supply - Hause, John C.; Du Rietz, Gunnar (Journal of Political Economy, 1984)
Entry is widely discussed but rarely subjected to empirical study. This study develops a competitive theory of entry, with primary focus on the relationship between entry and industry growth. The main ingredients are adjustment costs to firms already in the industry and the distribution of fixed entry cost to potential entrants. The theory suggests sufficient conditions under which the entry rate is an increasing, convex function of the industry growth rate. A regression model correcting for severe heteroscedasticity is applied to data from Swedish manufacturing industries. The results are consistent with the theoretical prediction for growth and other key variables expected to influence entry significantly.